PENGARUH SUKU BUNGA DEPOSITO, KURS RUPIAH-USD, TINGKAT INFLASI, IHSG DAN VOLUME TRANSAKSI TERHADAP HARGA OBLIGASI PEMERINTAH RI (SUN) - Eman Sukanto (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2009)
Government bonds, in the U.S. named T-Bone, in Indonesia called the SUN is the government’s financial instruments to absorb funds from the market. The objective is to close the budget deficit, helped the banking restructuring, or other funding needs that are considered important by the government. Bond investors are in great demand because it is safe (low risk).However, in addition to seeking safe, investors also expect a maximum return. Since 1999 until now the government has published a series of Government Bonds. This research will analyze the influence of deposit rates, the exchange rate of rupiah against the U.S. dollar, the inflation rate, JCI and the volume of transactions on the price of government bonds RI. Population of this research are fixed rate bonds which the government of Indonesia in the issue in 1999 until 2006 and maturity date of the year 2013. Price monitoring conducted over 36 months from October 2003 until September 2006. Technique of determining the sample with purposive sampling method. The sample was taken amounted to 10 items. The study concluded deposit rates have a significant effect on bond prices negatively. Rupiah exchange have a significant negative effect on bond prices. Inflation does not have a significant effect on bond prices. CompositeStock Price Index have a significant positive impact on bond prices, and transaction volume of bonds do not have a significant effect on the price of government bonds RI.